Structure Determination of Felodipine Photoproducts in UV-Irradiated Medicines Using ESI-LC/MS/MS - Kohei Kawabata; Miya Kohashi; Shiori Akimoto; Hiroyuki Nishi (MDPI AG, 2023)
Dihydropyridine drugs are well known as photodegradable pharmaceuticals. Herein, we evaluate the photostability of felodipine (FL) medicine (Splendil® (SPL) tablets) and its altered forms (powders and suspensions). FL is a type of dihydropyridine drug, but its photochemical behavior is unknown. FL contents after ultraviolet light (UV) irradiation for 24 h were monitored using high-performance liquid chromatography (HPLC). Values of the residual amounts of FL in UV-irradiated SPL powders and suspensions were 32.76 ± 4.88% and 0.79 ± 0.74%, respectively, with the generation of two photoproducts (FL photoproduct 1 and 2). To identify the chemical structures of these photoproducts, electrospray ionization liquid chromatography mass spectrometry (ESI-LC/MS/MS) analysis was performed. Based on their mass-to-charge ratio values and fragment patterns, it was proposed that FL photoproduct 1 was a pyridine derivative and FL photoproduct 2 was an FL dimer. Interestingly, generation rates of FL photoproduct 1 and 2 were dependent on the presence of the aqueous media. The photodimerization of FL was induced in UV-irradiated SPL suspensions. This is the first report evaluating the photostability of SPL tablets and its altered forms and estimating FL photoproducts induced by UV irradiation in the formulation of SPL.